Monitoring of Ozone Risk for Forests in the Czech Republic: Preliminary Results - Vít Šrámek; Radek Novotný; Emilie Bednárová; Hana Uhlírová (The Scientific World Journal)
Ozone (O3) is supposed to represent a significant risk for the health of forest ecosystems in Central Europe. So far, however, its impact on stands growing under natural conditions has not been clearly proved. A new project of the National Agency for the Research in Agriculture is focused on the O3 effect on selected parameters of forest health. This paper presents the results of the first year of monitoring, 2005. In 2005, high O3 concentrations were measured, mainly in the spring. In the summer, due to wet and cold weather, the O3 load was comparatively low. In the plots investigated, the concentrations of O3 were higher with the altitude. The amount of epicuticular waxes on 1-year-old Norway spruce needles was the only factor showing significant correlation to O3 concentration. Defoliation of the stands depended only on the stand age. The amount of malondialdehyde (MDA), an oxidative stress marker, was related to the altitude, and only for European beech. The results are preliminary, as the summer O3 development was not typical in 2005, and the results may change over the next monitoring periods.